The Higher Education and Salaries (Annual of the Faculty of Philosophy in Skopje, 2018)
Education is vital for dynamic growth and development. The higher education isimportant for every country. It is regulated by systemic regulations and bylaws. In this paper,the interest is directed at the salaries of employees in the state higher education, giventheir long-standing lag. The forms of payment of employees are analyzed and the salary levelis compared with the averages in the country. The paper proposes solutions that are ofimportance for this issue, especially for forming a payroll model that will correspond to themeaning of the educational segment of the society. The status of the professors as serviceproviders is inadequate and is not regulated from the aspect of the salaries and the benefitsfor the invested labour. Without motivated teachers and professors who implement thehigher education system, changes and results cannot be expected in terms of the quality ofhuman resources produced at universities. In the absence of a culture of appreciation of theknowledge, postulates are formed which in the long run cannot change the values of thesystems in society.
Keywords: HIGHER EDUCATION; SALARIES; REGULATION; PERCEPTION; OPPORTUNITIES